2015
DOI: 10.1007/s00394-015-1057-0
|View full text |Cite
|
Sign up to set email alerts
|

Associations of infant milk feed type on early postnatal growth of offspring exposed and unexposed to gestational diabetes in utero

Abstract: Purpose Infants on prolonged breastfeeding are known to grow slower during the first year of life. It is still unclear if such effects are similar in offspring exposed to gestational diabetes (GDM) in utero. We examined the associations of infant milk feeding on postnatal growth from birth till 36 months of age in offspring exposed and unexposed to GDM.MethodsPregnant mothers undertook 75 g 2-h oral glucose tolerance tests at 26–28 weeks of gestation for GDM diagnosis. Up to 9 measurements of offspring weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 51 publications
2
30
1
Order By: Relevance
“…In contrast to the current findings and findings of the above studies, a prospective cohort of 1152 Asian women with GDM (n = 181) in Singapore reported that offspring of mothers without GDM who were breastfed for at least 4 months had slower growth rate from birth to 36 months of age than those who were not breastfed or were BF for less than 4 months; however, they did not find similar results in offspring of mothers with GDM . In the GDM offspring, greater breast milk intake was associated with accelerated weight gain and BMI in the first 6 months of age.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to the current findings and findings of the above studies, a prospective cohort of 1152 Asian women with GDM (n = 181) in Singapore reported that offspring of mothers without GDM who were breastfed for at least 4 months had slower growth rate from birth to 36 months of age than those who were not breastfed or were BF for less than 4 months; however, they did not find similar results in offspring of mothers with GDM . In the GDM offspring, greater breast milk intake was associated with accelerated weight gain and BMI in the first 6 months of age.…”
Section: Discussioncontrasting
confidence: 99%
“…Only one prospective study previously measured growth during the first year of life among infants of GDM mothers. This study of 181 Singaporean infants found that breast milk intake for ≥4 months was associated with accelerated weight gain from birth to 6 months and higher attained BMI compared to no BF (16). Unmeasured confounding or reverse causation could explain these findings because early preterm births were not excluded, and the analysis did not account for effects of adverse newborn health outcomes or maternal GDM severity.…”
Section: Discussionmentioning
confidence: 97%
“…These studies showed mixed findings that do not support the previously reported protective associations between BF duration and subsequent development of overweight or obesity among children exposed to maternal diabetes in utero. A prospective study of 181 GDM infants found that BF ≥4 months accelerated weight gain from birth to 6 months compared with no BF (16), and a retrospective study of 94 youth exposed to maternal diabetes found a borderline lower body mass index (BMI) gain from birth to 9 months associated with 'adequate breast-milk months' (17). However, these studies did not account for reverse causation related to inclusion of early preterm infants (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Social support may only have limited success in mitigating these effects (33), and are less likely to succeed in communities with low breastfeeding prevalence like Singapore (34,35). Increasing awareness of the bene ts of breastfeeding for mother and infant, especially of the reduced long-term risk of metabolic conditions in breast-fed infants creates a stronger incentive to improve lactation through a multidisciplinary approach (35,36). Offspring of diabetic mothers are at an increased risk of developing impaired glucose tolerance themselves; there is evidence that the rst week of life appears to be the critical window period for nutritional programming in offspring of diabetic mothers (3).…”
Section: Discussionmentioning
confidence: 99%